Cover Picture: (Chem. Eur. J. 38/2016). Issue 38 (6th September 2016) - Unknown
Abstract : The 6th EuCheMS Chemistry Congress is being held in Seville from 11 to 15 September, 2016. Chemistry—A European Journal has put together a special issue for this occasion, with work from selected scientists presenting their results at the conference and also highlighting papers by Spanish research groups. The cover highlights work from several of the speakers, indicating the diverse range of chemistry that will be covered at the congress In the top row from left to right: L. M. Liz‐Marzán, R. Martínez‐ Máňez et al. (p. 13488 ff. ) from the symposium Materials, Devices and Nanochemistry, A. Company and T. Corona (p. 13422 ff. ) from the symposium New Chemical Compounds: Synthesis, Methods and Industrial Processes, C. Bo, J. de Mendoza et al. (p. 13496 ff. ) from the symposium Properties of Matter. In the middle row from left to right: N. Yan et al. (p. 13402 ff. ) from the symposium The Environment, Energy, and Sustainability, D. Monge, J. M. Lassaletta, R. Fernández et al. (p. 13430 ff. ) from the symposium New Chemical Compounds: Synthesis, Methods and Industrial Processes. In the bottom row from left to right: L. Cipolla and L. Russo (p. 13380 ff. ) from the symposium Materials, Devices and Nanochemistry, K. Kohse‐Höinghaus (p. 13390 ff. ) from the symposium Physical, Analytical and Experimental Methods in Chemistry, A. Hirsch et al. (p. 13506 ff. ) from the symposium Materials, Devices and Nanochemistry.